Pengaruh Gender Keberagaman Dewan Komisaris, Risiko Komite Manajemen, Leverage Dan Ukuran Perusahaan Terhadap Pengungkapan Manajemen Risiko Perusahaan - Lubis, Yuni Safitri; Martias, Dony (Jurnal Rumpun Ilmu Ekonomi, 2024)
This research is a quantitative study which aims to determine the This research aims to determine the influence of gender diversity of the board of commissioners, risk management committee, leverage and firm size on enterprise risk management disclosures in insurance companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The method used in this research is purposive sampling with a population of 18 companies and a sample of 17 companies. The data analysis method used is quantitative analysis, namely using Panel Data Regression analysis starting from descriptive statistical analysis, classical assumption testing, selection of panel data regression models, and hypothesis testing with the help of the EViews 12 computer program. The results of the research F test show the variable gender diversity of the board of commissioners , risk management committee, leverage and firm size simultaneously influence enterprise risk management disclosure. From this research, a coefficient of determination was obtained of 0.173516, which means that 17.35% of disclosure is explained by the gender diversity variables of the board of commissioners, risk management committee, leverage and firm size. And 82.65% is explained by other variables outside the model. Based on the t test results, the leverage variable has a negative and significant effect on enterprise risk management disclosure. Meanwhile, the gender diversity variables of the board of commissioners, risk management committee and firm size have no effect on enterprise risk management disclosure.